Staff Views of Acceptability and Appropriateness of a Computer-Delivered Brief Intervention for Moderate Drug and Alcohol Use - Mitchell, Shannon Gwin (J Psychoactive Drugs, 2015)
The use of computers for identifying and intervening with stigmatized behaviors, such as drug use, offers promise for underserved, rural areas; however, the acceptability and appropriateness of using computerized brief intervention (CBIs) must be taken into consideration. In the present study, 12 staff members representing a range of clinic roles in two rural, federally qualified health centers completed semi-structured interviews in a qualitative investigation of CBI vs. counselor-delivered individual brief intervention (IBI). Thematic content analysis was conducted using a constant comparative method, examining the range of responses within each interview as well as data across interview respondents. Overall, staff found the idea of providing CBIs both acceptable and appropriate for their patient population. Acceptability by clinic staff centered on the ready availability of the CBI. Staff also believed that patients might be more forthcoming in response to a computer program than a personal interview. However, some staff voiced reservations concerning the appropriateness of CBIs for subsets of patients, including older patients, illiterate individuals, or those unfamiliar with computers. Findings support the potential suitability and potential benefits of providing CBIs to patients in rural health centers.